Feasibility Investment Analysis On Development Telkom Landmark Tower Building At PT Telkom Landmark Tower - Husna, Qoriatul; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
PT Telekomunikasi Indonesian, Tbk (Telkom) intends for the consolidate entire operational activities Telkomsâ€™ office and subsidiaries which at this time some of them still rent office building to another party in Jakarta, to be united into one office building which will referred as Telkom Landmark Tower (TLT). To apply this program, the Board of Directors Telkom has assigned that the TLT will be built in land belonging to Telkom in Jalan Jendral Gatot Subroto, Jakarta. Property commercial industry, in particular office space on quarter IV-2012 in the Jabodebek experiencing positive development, it is indicated with increase in supply which followed with increase in occupancy rates and sales as well as tariff lease and price the selling. Based on the fact Telkom plans to build the building which can accommodate the needs office space for Telkom Group, hence it can decrease rent expense office buildings in Group. In conduct of feasibility investment analysis on the construction of TLT using capital budgeting method, with some approaches namely Payback Period, Net Present Value, Internal Rate of Return and Profitability Index. Based on the results of calculation and feasibility investment analysis using capital budgeting method obtained the result that the investment of the construction of TLT feasible to be implemented. Â Keywords: Capital Budgeting, Feasibility Investment Analysis